PENGARUH MOTIVASI KARIR, KECERDASAN ADVERSITY, PERTIMBANGAN PASAR KERJA, DAN FINANCIAL REWARDS TERHADAP MINAT BERKARIR SEBAGAI SEORANG AKUNTAN PUBLIK - Khaerunisa; Anggraeni, Rahayu; Kristanto, Eri (JURNAL EKONOMI, 2025)
This study aimed to test hypothesis the effect of career motivation, adversity quotient, labor market consideration, and financial rewards career interest as a public accountant. The type of this research is quantitative research using primary data, which is the the population of this research is from Universitas Jenderal Soedirman and Universitas Muhammadiyah Purwokerto students. The method used in this research is purposive sampling method which is the criteria of this research is student batch 2021 and has attend to auditing class. Based on the purposive sampling method that was calculate, 169 respondents obtained. The data in this research was processed using SPSS application and using multiple linear regression method, and in this research also used descriptive statistics, data quality test, classical assumption test, and hypothesis testing. The result of this research shown the career motivation, adversity quotient, labor market consideration, and financial rewards recognition positive effect on career interest as a public accountant.